Detection Rates of Bacteria in Chronic Otitis Media with Effusion in Children - Park, Chul-Won (The Korean Academy of Medical Sciences, 2004)
This study was performed to investigate polymerase chain reaction-based detection of bacterial DNA in middle ear fluid and assess the correlation between the PCR-positive rate with several factors associated with middle ear effusion. The purpose was to gain a further understanding of bacterial infection as a major cause of otitis media with effusion. Of the 278 specimens of middle ear fluid, 39 (14%) tested positive by ordinary culture. The overall detection rate of bacterial DNA using the PCR method was 36.7% for middle ear effusion, and bacterial DNA detection rates of Hemophilus influenzae, Streptococcus pneumoniae, Moraxella catarrhalis in the middle ear effusion were 29.1%, 4.7% and 10.8%, respectively. The bacterial DNA detection rate was higher in ears with a history of acute otitis media than those without the history. High detection rates were observed in patients younger than 48 months who have had a higher tendency to present with acute otitis media. We concluded that PCR is a more sensitive method for the detection of bacteria in middle ear effusion than ordinary culture, and acute otitis media is a major contributor to the pathogenesis of otitis media with effusion.